MgO NPs reinforced PCL/PVC nanocomposite films with enhanced UV shielding and thermal stability for packaging applications - Coskun, Meltem; Ozen Oner, Ecem; Tatar, Cengiz; Kok, Mediha (De Gruyter Poland Sp Z O O, 2025)
In this study, poly(epsilon-caprolactone) (PCL) and polyvinyl chloride (PVC) nanocomposite films reinforced with magnesium oxide (MgO) nanoparticles were successfully fabricated for potential use in UV-shielding packaging and optoelectronic applications. Composites containing 10, 20, and 30 wt% MgO were prepared via the solution casting method, and their structural, morphological, thermal, and optical characteristics were comprehensively analyzed using FTIR, XRD, SEM, DSC, TGA, and UV-Vis spectroscopy. FTIR and XRD results confirmed strong interfacial interactions between MgO nanoparticles and polymer chains, accompanied by a notable enhancement in crystallinity with increasing MgO content. SEM micrographs revealed uniform dispersion with limited agglomeration observed at 30 wt% MgO, supporting the morphological consistency of the composites. DSC and TGA analyses demonstrated that MgO acts as a nucleating and thermally stabilizing agent, leading to improved crystallization behavior and higher residual mass. Optical investigations indicated that MgO incorporation enhanced UV absorption capability and reduced the optical band gap from 5.77 eV (pure blend) to 4.88 eV (30 wt% MgO), confirming improved photon-matrix interaction. In addition, the films exhibited a reversible shape memory effect, allowing recovery of their original form after thermal stimulus. Considering their low density, environmental compatibility, and cost-efficient fabrication, MgO-reinforced PCL-PVC nanocomposites are proposed as promising, scalable, and economically viable materials for advanced packaging, biomedical, and flexible optoelectronic applications.
Keywords: PCL; PVC; MgO nanoparticles; nanocomposite; optical properties; thermal stability